Assessment of Quality Basic Police Education and Training In Ethiopia; The Case of Amhara Region Police College - Kefialew Yenyet Mitiku (Journal of Arts, Literature, Humanities and Social Sciences, 2023)
The purpose of this study was to assess the quality of basic police training in Ethiopia the case of the Amhara Region Police College. To achieve the objective of the study, mixed research approach was employed. Available sampling and purposive sampling techniques used to select respondents. The finding of study revealed that the quality of basic police education has been declining time to time by different factors. It is recommended that to avoid all factors that were contributing to the poor quality for basic police education and training, the management member of the college should continuously identify and solve those problems.